Advancements in Photodynamic Therapy: A Revolutionary Approach in Dentistry (Academia Journal of Medicine, 2023)
Photodynamic Therapy: A  Revolutionary Approach in  Dentistry. Acad J Med 2023;  6(1): 8-13. Photodynamic therapy (PDT) is a promising adjunctive  approach in dentistry. This abstract reviews the  current status of PDT in dental applications, focusing  on its antimicrobial efficacy, wound healing properties,  and potential for periodontal and endodontic  therapies. Highlighting the clinical implications and  future directions, it emphasizes PDT's non invasiveness and low cytotoxicity. Despite challenges,  PDT demonstrates potential as a valuable tool in  managing oral infections and promoting tissue  healing, presenting opportunities for further research  and clinical utilization.
Keywords: Photodynamic therapy; PDT; Dentistry